2022
DOI: 10.1016/j.oraloncology.2021.105439
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 negatively impacted on small oncology surgery but none on major procedures: Regional experience

Abstract: Aim to understand the impact of COVID pandemic on the activity and patients’ care of the Head and Neck regional Unit, temporary moved in a COVID-free hospital. Methods we retrospectively analyzed the yearly activity of the “Head & Neck Cancer Unit” at the Azienda Ospedali Riuniti Marche Nord (Italy) during 2020 (COVID-19 pandemic) and we compared it with the one performed in 2019. Statistical analyses were performed using Chi-square. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…For instance, in 2020, in Lombardy, one of the Italian regions most affected by the pandemic, an overall drop of 60.1% was shown, 20 suggesting that the epidemiological situation had a great influence on the impact on oncological surgeries. Moreover, the site‐specific significant reductions that we reported in Piedmont were different from results from other regions (e.g., in Southern and Central Italy significant reduction have been revealed for breast, thyroid, and skin cancer), 21,22 indicating discrepancies that cannot be explained solely by differences in the SARS‐CoV‐2 epidemiological context. It is possible that the observed differences are due to organizational disparities; therefore, it is crucial to further investigate organizational variations in service delivery and pathways for different types of cancer, to understand which reductions were avoidable and which organizational strategies were effective.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For instance, in 2020, in Lombardy, one of the Italian regions most affected by the pandemic, an overall drop of 60.1% was shown, 20 suggesting that the epidemiological situation had a great influence on the impact on oncological surgeries. Moreover, the site‐specific significant reductions that we reported in Piedmont were different from results from other regions (e.g., in Southern and Central Italy significant reduction have been revealed for breast, thyroid, and skin cancer), 21,22 indicating discrepancies that cannot be explained solely by differences in the SARS‐CoV‐2 epidemiological context. It is possible that the observed differences are due to organizational disparities; therefore, it is crucial to further investigate organizational variations in service delivery and pathways for different types of cancer, to understand which reductions were avoidable and which organizational strategies were effective.…”
Section: Discussioncontrasting
confidence: 99%
“…for breast, thyroid, and skin cancer), 21,22 indicating discrepancies that cannot be explained solely by differences in the SARS-CoV-2 epidemiological context. It is possible that the observed differences are due to organizational disparities; therefore, it is crucial to further investigate organizational variations in service delivery and pathways for different types of cancer, to understand which reductions were avoidable and which organizational strategies were effective.…”
Section: Discussionmentioning
confidence: 99%
“…Five out of seven published studies reported more advanced T-and N-stages of HNC patients during the pandemic [ 18 - 20 , 22 , 24 ]. Despite severe pressure on health services in northern Italy during the beginning of the virus spread, D'Ascanio et al [ 25 ] did not notice any shift to more advanced cancer stages during this period. These reports, even though geographically limited, indicate the negative side effects of the pandemic on public health.…”
Section: Discussionmentioning
confidence: 95%
“…Further exploration of HNC patient care in other Canadian centers during the pandemic, along with a prospective evaluation of this transparent model for patient-centered OR prioritization in those different settings, would help determine its role on the national level moving forward. The results are also limited in their comparison to other countries which utilize healthcare systems unlike the publicly funded single-payer system in Canada (Medicare), especially in terms of wait times and access to services [28][29][30]. For example, a study by Schoonbeek et al in the Netherlands, also found a decrease in the mean time to treat interval during the first wave of the pandemic, which they attributed in part to a decline in overall patient volume and national quality indicators for HNC patient care [31].…”
Section: Study Limitationsmentioning
confidence: 99%